Financial statement and budget report 1983-84 - Great Britain (Great Britain, Treasury / London, 1983)
This handbook contains a detailed financial statement including a budget reports between 1983-84. The paper further highlights medium and long term financial strategy.
asm; 10/04/19
Loans
Keywords: Finance, public; Taxation